Evaluation of Surface Runoff Estimation in Ungauged Watersheds Using SWAT and GIUH. (2016) - Iskender, Irshada; Sajikumar, N.
Abstract: Soil and Water Assessment Tool (SWAT) is a physically based distributed model that can estimate runoff, sediment and soil erosion from agricultural watersheds under different management conditions. The new SWAT has provision to simulate watershed process using sub daily rainfall. Though the model is generally meant for continuous modelling, the provision to make use of sub daily rainfall enables the model to be used for event modelling. GIUH is a methodology which can also be used for predicting the surface runoff from ungauged basins. On assessing the performance of these models in modeling of different events in Manali watershed, it is concluded that the GIUH method are marginally better than that from the SWAT model.